Electronic governance and its role in promoting entrepreneurship - a survey study of a sample of colleges at Sulaimani Polytechnic University - Yaba, Bezhan Hussein (Journal of University of Human Development, 2024)
This research aims to explain the role of electronic governance in its various dimensions in promoting entrepreneurship, by applying it in the colleges of Sulaimani Polytechnic University. To achieve the research objectives, the researcher collected data from various sources. The descriptive analytical approach was used to conduct the study, and the questionnaire was a main tool for collecting information. The research community consisted of college deans, assistant deans, department heads, department rapporteurs, division and unit officials, and professors. Their number reached 250 individuals, where 200 questionnaires were distributed and 49 questionnaires were returned. The total percentage of questionnaires received was 24.5%. SPSS program was used to analyze the data. The study reached a number of results, the most important of which is that the colleges of Sulaimani Polytechnic University give great importance to the variable of electronic governance in its various dimensions (Standards and applications, electronic participation, monitoring and evaluation, capabilities and human resources), and entrepreneurship in its various dimensions (creativity and innovation, initiative, take advantage of the opportunities, risk). The study found that there is a strong and direct correlation between electronic governance in its various dimensions and entrepreneurship. The research concluded that there is a need to activate the university’s great capabilities in implementing e-governance, through the presence of effective strategies to solve problems.